2007
DOI: 10.1016/j.ijosm.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the challenge of clinically relevant osteopathic research: Efficacy and beyond

Abstract: The osteopathic profession has been challenged over the past decade to provide clinically relevant research. The conduct of evidence-based osteopathic research is imperative not only for scientific, economic, and professional reasons, but also to drive health care policy and clinical practice guidelines. This paper summarizes recent studies in response to the osteopathic research challenge, including clinical trials registered with ClinicalTrials.gov and a systematic review and meta-analysis of osteopathic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…1 Clinical trials using rigidly defined and executed protocols have studied the efficacy of OMT in treating patients with such medical conditions during the past 2 decades. 3 This research has demonstrated the efficacy of OMT in treating patients with chronic low back pain 4,5 and has contributed evidence to establish and support the American Osteopathic Association's clinical guidelines for OMT in patients with low back pain. 6 There has been a recent move to assess clinical interventions such as OMT more pragmatically by determining their effectiveness and utility during actual patient encounters rather than in tightly controlled trials.…”
mentioning
confidence: 88%
“…1 Clinical trials using rigidly defined and executed protocols have studied the efficacy of OMT in treating patients with such medical conditions during the past 2 decades. 3 This research has demonstrated the efficacy of OMT in treating patients with chronic low back pain 4,5 and has contributed evidence to establish and support the American Osteopathic Association's clinical guidelines for OMT in patients with low back pain. 6 There has been a recent move to assess clinical interventions such as OMT more pragmatically by determining their effectiveness and utility during actual patient encounters rather than in tightly controlled trials.…”
mentioning
confidence: 88%
“…Osteopathic research, incorporating double-blinded studies, is warranted to ascertain the optimal treatment approach for rotator cuff tears in non-surgical candidates. The design and execution of such studies are inherently complex due to standard barriers associated with randomized-controlled trials as well as the additional challenges associated with osteopathic research which include the necessity of devising and implementing "sham therapy" to blind the operator [ 18 ]. Despite these challenges, this case report highlights the importance of continued research, especially in elucidating the specific mechanisms that can create optimal efficacy in shoulder pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, publications in this bibliometric study have been published in relatively low impact factor journals, which might impede the capacity of scholars to reach the overall healthcare community. Broader and better dissemination of research results through open access publications and various media can improve the reach to both patients and practitioners [ 46 ], for a greater impact in the healthcare field, including medical researchers, health care insurers, government agencies, and the media; the media is noted to exert considerable influence over public opinion and, potentially over policy [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%